MICRO RNA AS KEY REGULATORS IN ALLERGIC DISEASES: EPIGENETIC MECHANISMS AND DIAGNOSTIC POTENTIAL - Lisiecka, Maria Zofia (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Epigenetic therapy represents a promising approach for treating allergic diseases, with microRNAs (miRs) playing a crucial role as regulatory molecules in the immune response. The aim of this study was to systematize data on miRs to elucidate the molecular mechanisms of pathogenesis in allergic diseases. A meta-analysis of 61 studies published between 2017 and 2024 was conducted, focusing on specific miRs, their targets, biochemical interactions, model organisms, and health impacts related to different allergic diseases. The study identified key miRs such as miR-21, miR-151A, miR-155, miR-202-5p, and miR-375, which regulate inflammatory processes in allergic asthma, allergic rhinitis, atopic dermatitis, and urticaria. miRs such as miR-143-3p, miR-146a, and miR-221 have dual roles in modulating inflammation, depending on the tissue and disease stage. Additionally, miRs influence the differentiation of macrophages and T-helper cells, and the production of pro- and anti-inflammatory cytokines, which are critical to the pathogenesis of allergic diseases. Specific diagnostic markers were proposed for each disease, including miR-126, miR-133a, and miR-203 for asthma and atopic dermatitis. This analysis highlights the complex role of miRs in regulating allergic responses, offering potential therapeutic targets for miR-based interventions. The findings suggest that miRs could serve as biomarkers for diagnosis and prognosis of allergic diseases. Furthermore, the ability of miRs to both exacerbate and attenuate inflammation underscores their potential as therapeutic tools in precision medicine. The novelty of this study lies in the comprehensive synthesis of miR involvement in allergic diseases, providing a clearer understanding of their dual regulatory roles.